PENGENDALIAN PENYAKIT ANTRAKNOSA PADA TANAMAN CABAI MERAH MENGGUNAKAN AGEN HAYATI Trichodermaharzianum DAN Actinomycetes - Supriati L; Djaya A. A. (AgriPeat, 2016)
The research to study longevity and effectiveness involve agents Trichoderma harzianum and Actinomycetes to control anthracnose disease on red pepper. The research using Divice Complete Random consist 2 phase, phase 1) Examination of materials ajuvan at liquid potato dextrose (LPD) media to longevity involve agents T. harzianum and Actinomycetes with 6 treatment is 1) Actinomycetes culture in 250 mL LPD, 2) Actinomycetes culture in 250 mL LPD+1% corn flour (b/v), 3) Actinomycetes culture in 250 mL LPD+mollases 2% (v/v), 4) T. harzianum culture in 250 mL LPD, 5)T. harzianum culture in 250 mL LPD+1% corn flour (b/v), 6) T. harzianum culture in 250 mL LPD+mollases 2%, do at laboratory. Research of phase 2 to study involve agents T. harzianum and Actinomycetes to control anthracnose disease on red pepper, treatment involve agents culture in LPD 250 mL+1% corn flour media, consist 3 treatment that is: 1) no filtrat involve agents, 2) filtrat Actinomycetes 250 mL.L-1, 3) filtrat T. harzianum 250 mL.L-1, do at plastic house. Result of research show that addition of corn flour or mollases at LPD media improving population of T. harzianum until 2 w.a.i (week after inoculation) but decline at 3-4 w.a.i, while addition of corn flour improving population of Actinomycetes compared to mollasses, improving till 3 w.a.i but decline at 4 w.a.i. The control use filtrat T. harzianum and Actinomycetes to anthracnose disease show is same effectiveness with value effectiveness>69%.